MILDRONATE EFFECT ON ENDOTHELIUM-DEPENDENT VASODILATION IN PATIENTS WITH CHRONIC HEART FAILURE: DOUBLE BLIND CROSSOVER STUDY - L. G. Voronkov; A. A. I.Shkurat; E. A. Lutsak (Рациональная фармакотерапия в кардиологии)
Aim. To study effect of mildronate on stream-dependent vasodilation in patients with chronic heart failure (CHF).Material and methods. 30 patients with CHF taking standard therapy (diuretic, ACE inhibitor, β- blocker) as well as 30 healthy volunteers have been examined. Test of reactive hyperemia (RH) of brachial artery (BA) was performed in all patients. RH test was performed in patients with CHF in double blind crossover manner before and after infusion of NaCl-isotonic solution (placebo) or mildronate 1000 mg in NaCl-isotonic solution.Results. Increase in BA diameter (%∆D) in patients with CHF was less than this in control group (p<0,01) during RH test. After mildronate infusion increase in %∆D during RH phase was observed (from 8,6+0,8 to 14,4+0,9%, р><0,001). After placebo infusion BA diameter did not change significantly (from 9,3+0,7 to 10,4+0,8%, p>0,05).Conclusion. Mildronate improves endothelium-dependent vasodilation in patients with stable CHF.